Several stably expressed QTL for spike density of common wheat (Triticum aestivum) in multiple environments. (20th November 2019) - Liu, Hang; Ma, Jian; Tu, Yang; Zhu, Jing; Ding, Puyang; Liu, Jiajun; Li, Ting; Zou, Yaya; Habib, Ahsan; Mu, Yang; Tang, Huaping; Jiang, Qiantao; et al.
Abstract: Spike density (SD), an important spike morphological trait associated with wheat yield, is the spikelet number per spike (SNS) divided by spike length (SL). In this study, phenotypic data from eight environments were collected and a recombinant inbred line population (RIL) constructed by the wheat line 20828 and the cultivar 'Chuannong16' and a Wheat55K SNP array‐based constructed genetic linkage map were used to identify SD quantitative trait locus (QTL). Correlation between SD and other agronomic traits was calculated. Genes associated with plant growth and development for major loci were predicted. The results showed that 24 QTLs associated with SD were detected in eight environments. Among them, three major QTL, namely QSd.sicau‐5B.2, QSd.sicau‐2D.3 and QSd.sicau‐4B.1, explained up to 35.62%, 14.21% and 11.23% of phenotypic variation, respectively. The positive alleles of them were all derived from 'Chuannong16'. The significant relationships between SD and other agronomic traits were detected and discussed. Taken together, the stably expressed SD QTL under different environments identified in this study provided theoretical guidance for further fine mapping and germplasm improvement.